An age simulated virtual environment for improving elderly wellbeing - Zavlanou, Christina; Lanitis, Andreas (My University, 2016)
Aging effects cause significant changes in the functionality and abilities of the elderly that affect the overall interaction of elder people with their environment and other people. However, since the aging process occurs gradually in a person’s life, it is not possible for humans who belong to younger generations to experience the effects of aging. Towards this end we propose the use of a Virtual Reality (VR) based application that allows users to experience the effects of aging before such changes affect their body and mind. The proposed application targets two main objectives: The first objective is to allow product and software designers to experience problems faced by the elderly so that they design products friendly to older people. The second objective is to increase the appreciation and social inclusion towards the elderly. The development of this application relies on an extensive study of the literature that describes biological changes due to aging, so that several age-related effects are simulated in a VR environment in order to allow users to virtually experience life as an older person. During an experimental evaluation users were requested to complete a simple task in the age simulated VR-environment using a VR headset, and the reactions of the users were registered using appropriate questionnaires. The results of a preliminary investigation show that users can have a better understanding and appreciation towards older people after they are exposed in a VR age simulated environment.
Keywords: Active ageing; Aging effects; Product design; Social inclusion; Virtual Reality; Wellbeing